Admissibility of Requests for a Preliminary Ruling in the Case Law of the CJEU on Judicial Independence - Stanevičius, Mantas (Teisė, 2024)
In recent years, the CJEU has experienced a significant increase in requests for preliminary rulings on the interpretation of Article 19(1) TEU in the area of judicial independence. However, not all requests concerning this provision have been deemed admissible by the CJEU. This article examines the underlying principles of the preliminary ruling procedure under Article 267 TFEU that guide the CJEU in accepting or rejecting requests from national courts in this critically important area of EU law. It focuses on the concept of ‘court or tribunal’ within the meaning of Article 267 TFEU and the ‘necessity’ of the Court’s ruling.
Keywords: Rule of law; Principle of judicial independence; Tribunal previously established by law; Article 19(1) TEU; Article 267 TFEU; Article 47 of the Charter; Inadmissibility of requests for a preliminary ruling; Concept of ‘court or tribunal’; Necessity of the interpretation sought; Possibility to take account of the preliminary ruling